KOMPOSISI JENIS IKAN LAUT EKONOMIS PENTING YANG DIPASARKAN DI KOTA KUPANG - Naharuddin Sri; Yusuf Kamlasi (Partner, 2019)
Kupang City is one of the areas that has become the center of marine fish marketing in East Nusa Tenggara Province. Sea fisheries production in 2017 amounted to 25,262.27 tons consisting of 32 types of fish. Until now, information about important marine fish species and their marketing channels in Kupang City are still limited. The purpose of the research is to identificate and inventory important marine fish species and analyze their marketing channels. This research discusses in Kupang City from May to November 2019 The research locations were Oesapa Market, Oeba Fish Market, Pasir Panjang Fish Market, Kasih Market and Tenau Fish Landing Center. This research was conducted using the field survey method and literature review. Based on the results of the study data obtained by demersal fish species of 72 species, which are included in 42 genera and 29 families. Pelagic fish species numbered 38 species, which are included in 28 genera and 14 families. So the number of species of marine fish inventoryed and collected was 110 species consisting of 43 families and 70 genera. The types of sea fish are very important which are inventoried as many as 62 species of demersal fish and 38 types of pelagic fish. So a total of 100 important marine fish that have been successfully inventoryed and repaired are 100 species. For marketing channels, from the survey results, five (5) network marketing models for important marine fish products were obtained in Kupang City. There are 7 types of marketing institutions involved from producers to registered consumers: traders, sea collectors, land collectors, retailers, agents, end consumers, and exporters.  Keywords: marine fish, demersal, pelagic, economically important, marketing